The genus Cloeodes (Ephemeroptera: Baetidae) in Argentina with new generic synonymy and new species - Nieto, Carolina; Richard, Barton (Zootaxa, 2008)
Three new species of Cloeodes are described from Argentina (C. barituensis, C. espinillo and C. opacus), based on nymphs and from adults for the first two species. Two species, C. stelzneri and C. nocturnus, are proposed as nomen dubia. The only other species from Argentina, C. penai, is revised. The validity of the monotypic genus Bernerius is analyzed. A cladistic analysis including five species of the genus Cloeodes and Bernerius is presented and the synonymy of the latter is confirmed. A key for South American species of Cloeodes is presented.